Depresi dan Kesejahteraan Spiritual pada Ibu Hamil Risiko Tinggi - Handayani, Fitrias Putri; Fourianalistyawati, Endang (Jurnal Psikologi Teori dan Terapan, 2018)
This study aims to investigate the relationship between depression and spiritual well-being among women with a high-risk pregnancy. A quantitative method with correlational design was employed. Eighty-five participants were recruited for this study using accidental sampling technique. All participants were pregnant women with a high-risk pregnancy (between 24 and 36 weeks of gestation). Data were collected using two instruments, namely an adapted CESD-R (Center for Epidemiological Studies-Depression Scale Revised) to measure depression and an adapted Gomez & Fisher’s SWBQ (Spiritual Well-Being Questionnaire) to measure spiritual well-being. Results shows that there is a significant negative relationship between depression and spiritual well-being (r = -0,422 in the significance level of 0.01). It can be concluded from the result that the low level of depression correlates with the high spiritual well-being. Key words: Depression, spiritual well-being, high-risk pregnancyAbstrak: Penelitian ini bertujuan untuk melihat depresi dan kesejahteraan spiritual pada ibu hamil risiko tinggi. Metode penelitian ini adalah kuantitatif dengan desain korelasional. Dalam penelitian ini depresi dan kesejahteraan spiritual diukur dengan alat ukur yang telah diadaptasi, depresi diukur dengan Center For Epidemiological Studies - Depression Scale Revised (CESD-R) sedangkan kesejahteraan spiritual diukur dengan Spiritual Well-being Questionnaire (SWBQ). Pengambilan sampel dilakukan dengan teknik accidental sampling dan sebanyak 89 ibu hamil risiko tinggi dengan usia kehamilan diatas 6 bulan (24 – 36 minggu) menjadi partisipan dalam penelitian ini. Hasil menunjukkan terdapat hubungan yang signifikan dan bernilai negatif antara depresi dengan kesejahteraan spiritual sebesar r= - 0,422 (hubungan sedang) dengan signifikansi 0,01. Kesimpulan dari hasil penelitian ini adalah tingkat depresi yang rendah memiliki hubungan dengan kesejahteraan spiritual yang tinggi.